Pengaruh Lama Penyimpanan Terhadap Viabilitas dan Vigor Benih Kedelai (Glycine max L.) pada Suhu Kamar - Triati, Desfal (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Soybean (Glycine max (L.) Merrill) is a strategic crop requiring high-quality seeds to improve domestic production. However, soybean seeds have a limited storage life, especially at ambient temperature, which can reduce their physiological quality. This study aimed to identify the decline in seed quality during storage at room temperature. The experiment was conducted at the Agroecotechnology Laboratory, Universitas Andalas, using a Completely Randomized Design with two seed storage durations (3 and 6 months), each with four replications. Observed parameters included maximum germination potential, germination rate, vigor index, and germination uniformity. Results showed that seeds stored for 3 months maintained significantly higher physiological quality than those stored for 6 months. Maximum germination potential decreased from 85% to 25%, germination rate from 90% to 47%, vigor index from 47 to 6, and uniformity from 43% to 5%. It is concluded that soybean seed storage at ambient temperature should not exceed three months to preserve physiological quality. These findings provide important technical guidance for soybean seed management